Identification of soybean genotypes based on antixenosis and antibiosis to the armyworm (Spodoptera litura) - AYDA KRISNAWATI; MARIDA SANTI YUDHA IKA BAYU; M. MUCHLISH ADIE (Nusantara Bioscience, 2017)
Krisnawati A, Bayu MSYI, Adie MM. 2017. Identification of soybean genotypes based on antixenosis and antibiosis to the armyworm (Spodoptera litura). Nusantara Bioscience 9: 164-169. Armyworm (Spodoptera litura F.) is the main soybean leaf-feeding pest in Indonesia. A total of 10 soybean genotypes was identified for its resistance to armyworm through antixenosis and antibiosis tests. Genotype G100H was used as a resistant check. The experiment was conducted from April to July 2016 in Laboratory of Plant Breeding, Indonesian Legumes and Tuber Crops Research Institute, Malang, Indonesia and Laboratory of Optic, Faculty of Science and Technology, Universitas Islam Negeri Maulana Malik Ibrahim, Malang, Indonesia. Based on antixenosis resistance mechanism, two genotypes were resistant, two genotypes were moderately resistant, and six genotypes were susceptible to armyworm. Two resistant genotypes (G511H/Anj-1-4 and G100H) have short and dense trichome in the both of adaxial and abaxial positions. Those trichome orientation become a barrier for insect pests with chewing and biting type of mouth parts. Antibiosis resistance was evaluated based on armyworm growth. The lighter larval and pupal weight, and also a longer period of the larval and pupal stage were shown in two resistant genotypes which based on antixenosis test. Furthermore, the pupal weight seems to be more influential to the weight of larvae due to the mechanism of antibiosis. Hence, G511H/Anj-1-4 can be used as a source of the gene for improvement of soybean resistance to armyworm.